The use of Portlant cement related to occupational health. - Jorge, Gustavo Pires do Nascimento (Brazilian Journal of Production Engineering, 2023)
The present study aims to address the risks associated with exposure to cement in employees in civil construction. This is a field research carried out in the city of Imperatriz - Ma, in seven buildings of small and large size, constituting formal or informal. Despite the relevance of cement in civil construction, it is essential to be careful about the risks and pathologies associated with this chemical product, such as dermatosis, when the employee is exposed inappropriately, without proper personal protective equipment (PPE), lack of hygiene and unhealthy activities in direct contact with cement. Therefore, supervision when using appropriate PPE in work situations, in addition to risk awareness programs for employers, employees and society in general, contribute to the reduction of occupational diseases in civil construction.